2015
DOI: 10.1134/s1063784215060109
|View full text |Cite
|
Sign up to set email alerts
|

Fractal analysis of the 3D microstructure of porous materials

Abstract: Statistical and geometrical characteristics of the microstructure of the porous space of rock sam ples are investigated on the basis of 3D images obtained by X ray microtomography. It is shown that the sur face of the porous space exhibits fractal properties. As a result of fractal analysis of 3D micromodels, the lead ing fractal dimension, the multifractal spectra of generalized dimensions, and other structural and geometri cal parameters are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…This way, phase-retrieval can be coupled with process-based reconstructions [25,49] to create three-dimensional shapes during the packing process. Most importantly, in this work, we have explicitly shown that phase-retrieval can utilize more sophisticated structural statistics beyond the S 2 two-point correlation function -we tried SS 2 and C 2 so far, or other morphological metrics such as fractal dimensions [50,51]. This means that fast 3D reconstructions based on modified PR with the incorporation of other additional correlation functions can be used as input data for the SA algorithm [48] or building block for MPS reconstruction [6,20,52], as well as the abovementioned hybridization with process-based methods.…”
Section: Resultsmentioning
confidence: 99%
“…This way, phase-retrieval can be coupled with process-based reconstructions [25,49] to create three-dimensional shapes during the packing process. Most importantly, in this work, we have explicitly shown that phase-retrieval can utilize more sophisticated structural statistics beyond the S 2 two-point correlation function -we tried SS 2 and C 2 so far, or other morphological metrics such as fractal dimensions [50,51]. This means that fast 3D reconstructions based on modified PR with the incorporation of other additional correlation functions can be used as input data for the SA algorithm [48] or building block for MPS reconstruction [6,20,52], as well as the abovementioned hybridization with process-based methods.…”
Section: Resultsmentioning
confidence: 99%
“…sedimentary rocks [6], and rock structures [7]. The multifractal parameters find a relationship with the degree of cement hydration in cement paste [8], and multifractal behaviour of corroded steel surfaces has been observed also [9].…”
Section: Introductionmentioning
confidence: 91%
“…Отсутствие данных о величинах компонент гетероядер-ных связей в таких неметаллических материалах, как Al(OH) 3 , Ca 3 (Si 3 O 9 ) -волла-стонит, шунгит, связано с тем, что их определение является сложной фундамен-тальной задачей, которая для некоторых минералов практически не разрешима в силу их сложного химического состава. С увеличением степени ковалентности повышается энергия связи атомных остовов, что на макроуровне вызывает увеличение плотности вещества.…”
Section: характеристики исследуемых материалов и результаты определенunclassified